The Position of MSME Credit to Total Credit and its Effect on Digital Sales: A Case Study of 2015-2019 - Giantoro Pamungkas (Journal of Community Service and Engagement, 2023)
The Micro, Small and Medium Enterprises (MSMEs) sector plays a vital and important role in Indonesia's economy, contributing more than 60 percent to the Gross Domestic Product (GDP) and absorbing the majority of the national workforce. The availability of quality credit has been a key factor in advancing the MSME sector. However, the limited access to credit and the challenges faced by MSMEs trigger questions regarding the role of credit in supporting their transition to the rapidly growing digital market. This study aims to analyze the relationship between MSME credit position to total credit and its effect on digital sales in the period 2015 to 2019. The data used is sourced from the Central Bureau of Statistics (BPS) for MSME credit and total credit data, and from the Indonesian Internet Service Providers Association (APJII) and Google Temasek organizations for digital sales data. Multiple linear regression analysis was used to test the hypotheses of the study.The results show a positive and moderately influential correlation between the position of credit for MSMEs to total credit and digital sales. This finding indicates that MSME credit plays an important role in supporting MSME players to enter the growing digital market, improve competitiveness, and adopt digital technology. Therefore, this study has important implications for MSME players, financial institutions, government, and academics in an effort to improve economic growth and community welfare through the MSME sector in the digital era. Further research can be conducted to understand other factors that influence this relationship, such as business characteristics and consumer behavior.